New Frontiers of Anaerobic Hydrocarbon Biodegradation in the Multi-Omics Era - Laczi, Krisztián; Erdeiné Kis, Ágnes; Szilágyi, Árpád; Bounedjoum, Naila; Bodor, Attila; Vincze, György Erik; Kovács, Tamás; Rákhely, Gábor; Perei, Katalin (Frontiers in Microbiology, 2020)
The accumulation of petroleum hydrocarbons in the environment substantially endangers terrestrial and aquatic ecosystems. A number of microbial strains have been recognised to utilize aliphatic and aromatic hydrocarbons under aerobic conditions. Nevertheless, most of these pollutants are transferred by natural processes, including rain, into the underground anaerobic zones where their degradations are much more problematic. Even though aerobic bioremediation has been well-characterized over the past few decades, ample research is yet to be done in the field of anaerobic hydrocarbon biodegradation. With the emergence of high-throughput techniques, known as omics (e.g. genomics and metagenomics), the individual biodegraders, hydrocarbon-degrading microbial communities and metabolical pathways could be specified. Our objective is to review the anaerobic hydrocarbon biodegradation processes, the most important hydrocarbon degraders and their diverse metabolic pathways including the use of various terminal electron acceptors; describe the divergent anaerobic activation reactions; outline the key components known so far; explain the interactions between hydrocarbon-degrading community members; and provide a short outlook for effective applications of anaerobic bioremediation technologies.